If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3log(4x + -4) + 8 = 20 Reorder the terms: 3glo(-4 + 4x) + 8 = 20 (-4 * 3glo + 4x * 3glo) + 8 = 20 (-12glo + 12glox) + 8 = 20 Reorder the terms: 8 + -12glo + 12glox = 20 Solving 8 + -12glo + 12glox = 20 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -12glo + -8 + 12glox = 20 + -8 Reorder the terms: 8 + -8 + -12glo + 12glox = 20 + -8 Combine like terms: 8 + -8 = 0 0 + -12glo + 12glox = 20 + -8 -12glo + 12glox = 20 + -8 Combine like terms: 20 + -8 = 12 -12glo + 12glox = 12 Reorder the terms: -12 + -12glo + 12glox = 12 + -12 Combine like terms: 12 + -12 = 0 -12 + -12glo + 12glox = 0 Factor out the Greatest Common Factor (GCF), '12'. 12(-1 + -1glo + glox) = 0 Ignore the factor 12.Subproblem 1
Set the factor '(-1 + -1glo + glox)' equal to zero and attempt to solve: Simplifying -1 + -1glo + glox = 0 Solving -1 + -1glo + glox = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -1glo + 1 + glox = 0 + 1 Reorder the terms: -1 + 1 + -1glo + glox = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1glo + glox = 0 + 1 -1glo + glox = 0 + 1 Combine like terms: 0 + 1 = 1 -1glo + glox = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4x^2-2x-14=0 | | 4y=25 | | t+15=t(t-1) | | -5m+2=12 | | 2a+7b-7a-2b= | | 3n+6p+6n-p= | | 3=4x-13 | | 64-2x=9x-20 | | 5x-7=77-2x | | 8/5w=40 | | w^2-2w^2-12w-36=0 | | 1/3(x-6)=2 | | 4x^2-5x+13=8x+4 | | 9x^2-12x-32=0 | | 5x-6=8x+9 | | 5(4x-4)=5(x+5) | | 7v(v-7)=13v+9 | | x^2-6x+14=3x-4 | | 4(3x-2)=2(3x-5) | | (2v-5)(7v+1)=9v^2-60v-33 | | 9(x-2)=5(x+3) | | x^2+6x+16=8 | | 2(x+10)=50-x | | 3(x-5)=2x+5 | | 3-8u-3u^2=0 | | (x+7)(x^2-5x+3)=0 | | 4-6x=-5x-3 | | T^2-4=3t | | 2w^2-w^2-w-9=0 | | 35+17x=x+3 | | 8x+2=9x-10 | | ½-3x=6,5+½x |